1969
DOI: 10.1111/j.1365-2494.1969.tb01090.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Tiller Populations of Grass and Grassjclover Swards With and Without Irrigation

Abstract: The number of tillers per unit area of pure swards of S23 and S24 perennial ryegrass, S37 cocksfoot, S48 timothy and of a S23 perennial ryegrass/wiite clover sward, were examined at intervals of 4 weeks during a period of two years. The monthly appearance of new tillers and the death of tillers of S23 and S24 ryegrass and S48 timothy were followed for 15 months. The studies were made with and without irrigation. The number of tillers varied with season through the year. Tiller numbers increased rapidly in late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

1980
1980
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
3
23
0
2
Order By: Relevance
“…2). Similar results have been observed in the United Kingdom (Garwood 1969;Wade 1979;Tallowin 1981;Colvill & Marshall 1984). Korte (1986) andL'Huillier (1987) did not find such a flush during autumn in New Zealand, although Korte & Chu (1983) did observe a period of rapid tillering in autumn during recovery of tiller populations depleted by summer drought.…”
Section: Tiller Population Densitysupporting
confidence: 85%
See 1 more Smart Citation
“…2). Similar results have been observed in the United Kingdom (Garwood 1969;Wade 1979;Tallowin 1981;Colvill & Marshall 1984). Korte (1986) andL'Huillier (1987) did not find such a flush during autumn in New Zealand, although Korte & Chu (1983) did observe a period of rapid tillering in autumn during recovery of tiller populations depleted by summer drought.…”
Section: Tiller Population Densitysupporting
confidence: 85%
“…The rate of growth of the sward, being the integral of the growth rates of the component tillers, is influenced by the rate of tiller production as well as the growth rates of individual tillers (Milthorpe & Davidson 1966). Garwood's (1969) British study of tillering in perennial ryegrass indicated peaks of tiller appearance in spring and autumn. In another British study under a very infrequent defoliation regime (Colvill & Marshall 1984), there is evidence of a major tiller appearance event at or shortly after flowering.…”
Section: Introductionmentioning
confidence: 98%
“…In past studies of grass sward behaviour, processes of leaf, tiller, or root formation have usually been examined as distinct entities, e.g., Bircham & Hodgson (1983) and Parsons et al (1983) (leaf formation and death); Langer (1963), Langer et al (1964), Garwood (1969), and Korte (1986) (tiller population demography); and Garwood (1967), Caradus & Evans ( 1977), and Matthew ( 1992) (root dynamics). Although the reasons for studying these different processes separately have probably been logistical rather than philosophical, the practice of focusing on a particular sward process in major studies has resulted in a lack of attention to understanding the ways these processes interrelate.…”
Section: Introductionmentioning
confidence: 99%
“…This contention is supported by the work of Garwood (1969), who found that during the winter few daughter tillers entered the population of established L. perenne swards, and that tiller deaths also were low. In the present study, no effect was observed on pasture yield for the single harvest taken in 1982, but there were significant differences at the time of this harvest in the reproductive development between the swards.…”
Section: Long-term Effectsmentioning
confidence: 78%